Analysis of Financing Mechanisms and sources of budget Formation of the Testing Centers of the Complex “Ready for labor and Defense” - O. I. Samarchenko; D. G. Stepyko; D. V. Gracheva; D.A.O. Farzaliev (Финансы: теория и практика, 2023)
The Russian physical culture and sports complex “Ready for labor and defense” is established in Russia since 2014. The main element of the project is testing centers, of which more than 2600 in the country. At the same time, the activities of such centers are often not systematized and have different, sometimes diametrically opposite approaches to its organization. The subject of this study is the activities of testing centers, including personnel, financial, logistical and informational parameters. For several years, the federal operator is developing various methodological materials for the development of testing centers. The purpose of this study is to develop financing mechanisms for the identified forms of organization of testing centers. The main research methods are the statistical method and the method of comparative analysis. As part of our research, we analyzed statistical information for the period 2020–2022, as well as a survey of 170 testing centers located in 59 regions of Russia and having different organizational and legal forms and a number of other different features. Based on the results of the study, the main sources of financing for the activities of testing centers were identified, as well as mechanisms and recommendations for increasing budgetary and extra-budgetary funding of various activities of testing centers were developed. The results of the study are practical, tested, successfully applied by some organizations and can be used in testing centers of various types.